The Developmental of Guidance and Counseling in Elementary School - Dina, Risma; Farozin, Muh (Universitas Ahmad Dahlan, 2020)
This study aims to produce guidance and counseling programs in elementary schools. This research is development research following the procedure of the Borg & Gall model. The subject of validation was carried out by two competent experts in the guidance and counseling program and 3 class teachers as practitioners. The data collection instruments used were expert validation questionnaires, practitioner validation questionnaires, and guidelines for focus group discussion. The data analysis technique used is quantitative descriptive analysis techniques using categorization. The results of expert validation on the program and the results of practitioner validation of the program get a good category. It can be concluded that the guidance and counseling program in elementary schools is good and feasible to implement with several revisions given. The results of this study can be used as a development program for guidance and counseling services in elementary schools.